1990
DOI: 10.1002/aic.690360714
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive‐predictive control of kamyr digester chip level

Abstract: Kamyr digester chip level poses a difficult control problem, because the chip column dynamics are complex and it is difficult to measure the chip-liquor interface. Control of the chip level is required to smooth digester operation and to stabilize the residence time. Conventional methods rely largely on fixed parameter controllers which are unable to compensate for changes in the process dynamics. Manual controller retuning is often required.An adaptive chip level controller based on Generalized Predictive Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Control of continuous pulp digesters has been widely studied by both academic and industrial researchers. Initially, the research focus was set on the control of the chip level of continuous pulp digesters [104,106,107]. Eventually, the focus shifted to achieving maximum pulp production at a specific Kappa number with minimum chemical and energy consumption.…”
Section: Discussion and Future Research Directions Of Pulp Digesters mentioning
confidence: 99%
See 1 more Smart Citation
“…Control of continuous pulp digesters has been widely studied by both academic and industrial researchers. Initially, the research focus was set on the control of the chip level of continuous pulp digesters [104,106,107]. Eventually, the focus shifted to achieving maximum pulp production at a specific Kappa number with minimum chemical and energy consumption.…”
Section: Discussion and Future Research Directions Of Pulp Digesters mentioning
confidence: 99%
“…Dumont et al [104] and Belanger et al [105] showed self-tuning regulators (STR) using both chip feed and blow flow rate had comparable performances for Kamyr digester level control. Allison et al [106,107] demonstrated a MISO generalized predictive control (GPC) where the blow flow and the chip feed rate were manipulated simultaneously to control the chip level. However, the controller was discontinued after six months of operation due to increased Kappa number variability.…”
Section: Chip Level Controlmentioning
confidence: 99%
“…The noise created a bias at one, but even if this was ignored, the data gave an inconsistent delay estimate, ranging between two and four. While this was in the range of likely values [16], there is no guarantee that the estimated change was actually due to a change in the delay and was not actually caused by the disturbance. As a result, a delay of two sampling intervals suggested in [ 161 as occurring most often will be used to determine $La.…”
Section: B Kamyr Digester Chip Levelmentioning
confidence: 92%
“…Besides Kappa number, chip level is another important control variable, which effects the residence time of the chips in the reactor, and hence the extent of delignification process. Much research has been focused on chip level control (Allison, Dumont, Novak, & Cheetham, 1990;Wells, 1990). Although strong correlation exists between the chip level and the Kappa number, it is already realized that controlling the chip level tightly does not lead to good Kappa number control (Allison et al, 1990).…”
Section: Article In Pressmentioning
confidence: 99%
“…Much research has been focused on chip level control (Allison, Dumont, Novak, & Cheetham, 1990;Wells, 1990). Although strong correlation exists between the chip level and the Kappa number, it is already realized that controlling the chip level tightly does not lead to good Kappa number control (Allison et al, 1990). In this study, the cooking temperature is used to control the Kappa number, while chip level control is achieved through manipulations of the blow flow.…”
Section: Article In Pressmentioning
confidence: 99%